A STUDY ON DATA OF RETAIL BANKING - Sharam , Siddarth Ganesh Prasad Sharam; Shewale, Bhojraj (International Journal of Research -GRANTHAALAYAH, 2025)
Retail banking has emerged as a foundational pillar of India’s financial system, influencing economic inclusion, credit penetration, and financial stability. This study examines the retail banking operations of DCB Bank through primary observations gathered during a six-week internship. The research evaluates customer servicing, CASA performance, digital banking adoption, compliance mechanisms, lead generation, and branch-level operational efficiency. Using qualitative observation and quantitative insights derived from customer interactions and cold-call responses, the study identifies key strengths and constraints in retail branch functioning. Findings suggest that DCB Bank demonstrates strong customer service and compliance discipline but faces challenges in digital adoption and lead conversion. The paper concludes with recommendations to enhance digital literacy, streamline documentation, and integrate automated CRM procedures for improved performance.